(untitled) (Research, Society and Development, 2021)
The Joint Accommodation is the place where the woman and the healthy newborn, after birth, remain full time together, until hospital discharge. One of the benefits of Joint Accommodation is the possibility for the nursing professional to encourage the strengthening of self-care and newborn care, through health education activities developed during the assistance provided during the hospitalization period of the mother / child. Taking into account the recommendations of the Health Organs regarding the importance of breastfeeding, it is essential that the assistance provided in the Joint Accommodation involves guidance and assistance to the puerperal woman in the practice of breastfeeding. This is an experience report developed during the practices of the Supervised Internship discipline of the undergraduate nursing course, in the Joint Accommodation of a hospital located in a medium-sized municipality in the Central region of the State of Rio Grande do Sul. the assistance provided to the puerperal woman still needs to happen in the hospital environment, that is, in the Joint Accommodation, where the first changes are recognized, such as labor stress, pain, the beginning of the breastfeeding process, fear, insecurity, dependence and feelings of ambivalence. The objective of this work was to report the experience of a nurse during her academic training, on the importance of puerperal nursing care developed in the Joint Accommodation directed to the care of the mother / child binomial.